Europe Within the World of Regionalisms - Bach, Daniel C. (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
The surge of diversified forms of regionalism and regional integration within the past few decades has stimulated the reappraisal of the conceptual tools traditionally designed to benchmark and monitor region-building processes across the world. More recently, the Brexit negotiations have become a reminder that the EU remains an unfolding experience. This article argues that the study of African regionalisms constitutes a timely invitation to revisit the experience of the EU and its contribution to the world of regionalisms. After a brief survey of the classic definition of the region, we will discuss the ongoing relevance of European integration and the implications of the analytical distinction between regionalism, regionalisation and regional integration, before drawing from the study of Africa five threads which set the basis for a comparative study of regions and regionalisms beyond the classic emphasis on the EU or the world of regions.

Powstanie różnorodnych form regionalizacji oraz integracji regionalnej w przeciągu ostatnich dekad stymulowało ponowną ocenę konceptualnych narzędzi, tradycyjnie skonstruowanych w celu tworzenia punktów odniesienia oraz monitorowania procesu regionalizacji na świecie. Negocjacje w sprawie Brexitu przypomniały, iż sama Unia Europejska pozostaje zmieniającą się rzeczywistością. Główna teza poniższego artykułu zakłada, iż studiowanie Afrykańskich procesów regionalizacji stanowi zaproszenie do ponownego przeanalizowania doświadczeń Unii Europejskiej oraz jej miejsca w świecie regionalizacji. Po krótkim przeglądzie klasycznych definicji regionu, omówione zostanie współczesne znaczenie integracji europejskiej oraz implikacji rozróżnienia regionalizmu, regionalizacji oraz integracji regionalnej. Przed wyciągnięciem wniosków płynących ze studiowania Afrykańskich regionalizmów, przedstawione zostanie pięć kategorii, które stanowią podstawę badań wychodzących poza klasyczne spojrzenie na Unię Europejską oraz świat regionów.
EUROPA W ŚWIECIE REGIONALIZMÓW
Keywords: regionalism; regional integration; Europe; Brexit; EU; Africa; regionalizacja; integracja regionalna; Europa; Afryka; UE